E-VILLAGE BUDGETING : EFEKTIVITAS PENCEGAHAN FRAUD PADA PENGELOLAAN KEUANGAN DESA DI KABUPATEN BANYUWANGI - Satia Utama, Anak Agung Gde; Zahari, Afika Rana (JURNAL AKUNTANSI DAN AUDITING, 2019)
This study aims to examine whether the current village financial management system in Banyuwangi that uses E-Village Budgeting has been effective in preventing the possibility of fraud in managing village finances. The theories construct these researches are the fraud triangle theory, the fraud management process and ISO 9126. This study used qualitative exploratory methods. This study used the most common data analysis techniques, Max Weber's ideal type. This type is a model or mental abstraction of relationships or social processes. The typical variety is a clear standard where data or "reality" can compare. EVB effectiveness testing is done using ISO 9126. The result of this study is the village government feels that the current EVB system has been effective in preventing fraud in village financial management. This is because EVB has a different mechanism than when it is still manual, in the process of disbursing funds. This research can be used as a basis for further research on EVB and can be an input for the Banyuwangi government in taking additional EVB development policies.